Bilateral subdural hygromas following administration of intrathecal methotrexate chemotherapy. (22nd May 2015) - Lewis, Heledd; Mahdi, Ali Jassem; Rowntree, Clare
Abstract : We report the case of a previously well 58-year-old man who presented with headache and confusion 4 days postadministration of intrathecal methotrexate. He was undergoing intensive chemotherapy (CODOX-M/IVAC, cyclophosphamide, doxorubicin, vincristine, methotrexate, etoposide, ifosfamide, cytarabine) for the treatment of leukaemic phase CD20 negative diffuse large B-cell lymphoma. A CT of the head demonstrated the presence of bilateral subdural hygromas complicated by haemorrhage resulting from coexisting chemotherapy induced thrombocytopenia. Surgical drainage of the hygroma was undertaken but the patient died of overwhelming sepsis. In patients with high-risk lymphoma, directed central nervous system (CNS) therapy is administered either systemically or intrathecally. It is thought that subdural hygromas result from cerebrospinal fluid (CSF) accumulation in the inner dural layers of the cerebral convexities from CSF leak and reduction in CSF pressure post-lumbar puncture. We describe a rare but potentially fatal complication of intrathecal chemotherapy that haemato-oncologists need to be mindful of.